2004
DOI: 10.1007/s10350-004-0659-z
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation Volume Determines the Efficacy of “Rectal Washout”

Abstract: The irrigation volume determined the efficacy of rectal washout. With our method, 1 1/2 liters of saline irrigation appears to clear contents from cancer cells in patients with tumors below the peritoneal reflection whereas at least 2 liters is recommended for patients with tumor above the peritoneal reflection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 21 publications
2
42
0
3
Order By: Relevance
“…Alternatively, it may be just another manifestation of neoplastic progression when tumour starts producing autonomous potentially metastatic cells ready for secondary implantation. The latter assumption is corroborated by the cited reports of secondary anal metastases after removal of primary colorectal cancers [33][34][35] or peritoneal cancer dissemination during operations. 36 However, the 2 mechanisms are likely to be inseparably entangled since well-preserved colonocytes, apoptotic cells and cell debris are all abundant in the mucocellular layer of cancer patients.…”
Section: Cell Exfoliation In the Colonic Epithelium: Its Role In Normsupporting
confidence: 61%
See 1 more Smart Citation
“…Alternatively, it may be just another manifestation of neoplastic progression when tumour starts producing autonomous potentially metastatic cells ready for secondary implantation. The latter assumption is corroborated by the cited reports of secondary anal metastases after removal of primary colorectal cancers [33][34][35] or peritoneal cancer dissemination during operations. 36 However, the 2 mechanisms are likely to be inseparably entangled since well-preserved colonocytes, apoptotic cells and cell debris are all abundant in the mucocellular layer of cancer patients.…”
Section: Cell Exfoliation In the Colonic Epithelium: Its Role In Normsupporting
confidence: 61%
“…The findings were perfectly in line with clinical reports describing secondary distal, especially anal, tumours in colorectal cancer patients. [33][34][35] Such tumours, albeit rare, appear to result from an unusual metastatic process involving the reimplantation of viable exfoliated malignant cells migrating within the mucocellular layer. Likewise, occasional intraperitoneal seeding of exfoliated cancer cells during surgery for colorectal cancer can lead to peritoneal carcinomatosis.…”
Section: Cell Exfoliation In the Colonic Epithelium: Its Role In Normmentioning
confidence: 99%
“…Data from clinical and experimental studies show that irrigation fluid from the rectal stump contains a large number of exfoliated tumour cells 30,31 , which in vitro and in an immunosuppressed animal model have the potential for further growth 32,33 . Other studies have shown that exfoliated tumour cells are regularly found on stapling devices and may be implanted on the staple line 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Although rectal washout has been reported to eliminate exfoliated malignant cells [3,4,15,16], no data indicating a reduction of anastomotic implantation have been demonstrated [17,18]. Furthermore, this study was unable to Although it remains controversial in regard to whether an intensive follow-up program including rectosigmoidoscopy can improve survival [19,20], intensive flexible rectosigmoidoscopy is recommended in the guidelines for colorectal cancer surveillance [21,22].…”
Section: Discussionmentioning
confidence: 66%